Adverse effects on health and well-being of working as a doctor: views of the UK medical graduates of 1974 and 1977 surveyed in 2014 - Smith, F; Goldacre, M; Lambert, T (SAGE Publications, 2017)
Objective: To report on the views of general practitioners compared with other medical practitioners regarding career prospects. Design: Questionnaire survey. Setting: UK Participants: UK medical graduates from nine graduation years between 1974 and 2008, surveyed at various stages of their careers (19 surveys between 1996 and 2013). Main outcome measures: Responses about future career prospects. Results: Over all surveys, GPs had similar levels of satisfaction with their prospects as other doctors (surgeons 68% satisfied, GPs 71%, hospital medical specialties 70%, other hospital doctors 75%). Dissatisfaction with prospects was lowest among GPs, at 8%, and highest among surgeons, at 14%. However, with increasing time since graduation and increasing levels of seniority, GPs became less satisfied with their prospects: the reverse was true for surgeons. More women GPs than men GPs were satisfied with their future career prospects; this difference was in the opposite direction in the other specialties. Women GPs were more likely to be satisfied with their future prospects than women working in hospital medical specialties and surgery. Men doctors working in other hospital specialties were more likely than men GPs to agree that they were satisfied with their future career prospects. Conclusions: The profile of satisfaction with prospects is broadly positive for GPs as it is for other doctors. However, there is an increase in negativity with increasing seniority and time since graduation which is not seen in hospital doctors. Research into the causes of this negativity and policy measures to ameliorate it would contribute to the continued commitment of GPs and may help to reduce attrition.